Sleep disturbances in Alzheimer's disease and other dementias - Vecchierini, Marie-Françoise (Psychologie & neuropsychiatrie du vieillissement, 2010)
Sleep in dementias has been mainly studied in Alzheimer disease (AD). Sleep disturbances are found in 25 to 35% of subjects with AD. Subjective and objective disturbances are described. Long nocturnal awakenings disrupt sleep; total sleep time and sleep efficiency are reduced. Slow wave sleep is decreased and sometimes disappears. REM sleep percentage is also reduced and at a later stage of the disease, REM latency is increased. Sleep fragmentation can be associated with excessive daytime napping and sleepiness, and with other behavioral symptoms such as the sundowning syndrome and nocturnal agitation. Sleep abnormalities closely parallel the level of severity of dementia. The rest/activity ratio and the sleep-wake rhythms are more and more disturbed; the phase delay of the temperature rhythm is associated with the severity of the sundowning syndrome. Sleep disturbances and behavioral symptoms are the main reasons to institutionalize the patient. Sleep disturbances are related to multiple factors. Pathophysiological changes resulting of the disease itself, such as damage to the cholinergic pathways and to the circadian pacemaker in the suprachiasmatic nucleus, contribute to sleep changes in AD. Associated medical and psychiatric illness and their different treatments as well as environmental factors also induced sleep disturbances. Sleep-disordered breathing is a highly prevalent condition in AD patients and restless leg syndrome may account for nocturnal agitation. In Parkinson and in Lewy body dementias, sleep disturbances are more severe than in DA and REM sleep behavior disorder can precede by several years these diseases. Sleep attacks and sleepiness are very frequent in Parkinson disease. Specific etiologies should drive specific treatment. Several non pharmacologic treatments are usually associated to treat sleep disturbances in AD: information, increased daytime physical, social activities to minimize daytime naps and exposure to bright light. Some studies found advantages to associate melatonin in the evening.